Seasonal cyclical changes in the gonadal activity of common carp, Cyprinus carpio Linn - Guha, Dhriti; Mukherjee, Dilip (Indian Journal of Fisheries, 2011)
Annual reproductive cycle including cyclic changes in ovarian and testicular activity have been studied in several teleosts in relation to their environmental regulation (Billardef fl/. 1978, Peter and Crim 1979, Lam 1983, Scott and Sumpter 1983, Kaneko and Hanyu 1985, Mukhopadhyay and Sinha 1986). Common ceap, Cyprinus carpio, is an extensively cultivated species with 2 breeding periods, one during mid January to February and other during July to August (Alikunhi 1966, Jhingran 1985)